Rules and discretion in international policy - Guitian, Manuel (IMF WashingtonUS, 1992)
Looks at the periodic swings between those international economic regimes that have emphasized well-established rules to govern economic policy and those that have stressed the use of discretion in economic management. Examines the limits and opportunities facing units in an integrated system from the standpoint of the international debt crisis. Focuses on the international debt crisis. Examines the continuing effort to create a Single European Economy.